2007
DOI: 10.3133/sir20075144
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline-Related Compounds in Lakes Mead and Mohave, Nevada, 2004-06

Abstract: The distribution of man-made organic compounds, specifically gasoline-derived compounds, was investigated from 2004 to 2006 in Lakes Mead and Mohave and one of its tributary streams, Las Vegas Wash. Compounds contained in raw gasoline (benzene, toluene, ethylbenzene, xylenes; also known as BTEX compounds) and those produced during combustion of gasoline (polycyclic aromatic hydrocarbon compounds; also known as PAH compounds) were detected at every site sampled in Lakes Mead and Mohave. Water-quality analyses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…Th e PAHs likely come from in-lake sources, such as boats, where higher concentrations should be concentrated at the surface of the lake. Lico and Johnson (2007) have shown that boat traffi c is the major source of PAHs in Lake Mead, and our study shows that the highest concentrations in LVB occur near the surface of the lake, indicating boats as the likely source. Concentrations of PAHs are high at the surface of the lake even though volatilization and photolytic degradation of PAHs lowers the concentration of many PAHs near the surface of the lake (Lico and Johnson, 2007).…”
Section: Vertical Distribution Of Hydrophobic Contaminantssupporting
confidence: 49%
See 1 more Smart Citation
“…Th e PAHs likely come from in-lake sources, such as boats, where higher concentrations should be concentrated at the surface of the lake. Lico and Johnson (2007) have shown that boat traffi c is the major source of PAHs in Lake Mead, and our study shows that the highest concentrations in LVB occur near the surface of the lake, indicating boats as the likely source. Concentrations of PAHs are high at the surface of the lake even though volatilization and photolytic degradation of PAHs lowers the concentration of many PAHs near the surface of the lake (Lico and Johnson, 2007).…”
Section: Vertical Distribution Of Hydrophobic Contaminantssupporting
confidence: 49%
“…Th e reason for this is not clear but may be due to discharge of unburned petroleum products from boat exhaust from boats with two-stroke engines near the site. It is unlikely that the high values of petrogenic PAHs were caused by the boat used to deploy and retrieve the samples because the same boat was used at each site and it has a four-stroke engine, which would be less likely to discharge unburned fuel into the lake than a two-stroke engine (Lico and Johnson, 2007). Th e LVB site at 8 m depth showed the same SOCs (if detected) as the Outlet site (Tables 3 and 4) but at lower concentrations.…”
Section: Las Vegasmentioning
confidence: 99%
“…From 2004 through 2006, SMPDs were used to collect samples to investigate the distribution of gasoline-derived VOCs in Lakes Mead and Mohave (Lico and Johnson, 2007). Most of these compounds are toxic to varying degrees.…”
Section: Volatile Organic Compounds Related To Boatingmentioning
confidence: 99%
“…Studies by Lico and Johnson (2007) at Lakes Mead and Mohave, and by Lico (2004) at Lake Tahoe (Calif. and Nev.), showed that two-stroke gasoline engines can release up to 40 percent of their fuel into water bodies and are a major source of gasoline-derived organic compounds. In response to these and other studies, the National Park Service is phasing out the use of two-stroke engines that do not use direct injection within LMNRA by 2013 (http://www.nps.gov/lake/ parkmgmt/twostroke.htm).…”
Section: Volatile Organic Compounds Related To Boatingmentioning
confidence: 99%
See 1 more Smart Citation